PKP-PK Personnel Management Development Study at Halim Perdanakusuma Airport PT. Angkasa Pura II (persero) in Maintaining Competence and Airport PKP-PK Licenses - Alfiyah, Sifa; Harmoni, Ati (Dinasti International Journal of Digital Business Management, 2022)
PKP-PK Personnel Management Development Study at Halim Perdanakusuma Airport PT. Angkasa Pura II (persero) in Maintaining Competence and Licenses. Thesis 2022. Sifa Alfiyah. NPM 91620040. Based on the Regulation of the Director General of Civil Aviation KP 14 of 2015, Chapter III Paragraphs 1 and 3 states that each airport is required to provide PKP-PK personnel who have the licenses required by the Directorate General in accordance with the airport category for PKP-PK and PKP-PK personnel are required maintain competence, license, and health. So this study aims to determine the organizational structure, number of personnel, competence and licenses of PKP-PK personnel, and efforts made to maintain competence and licenses. The object of this research is the PKP-PK unit at Halim Perdanakusuma Airport PT. Angkasa Pura II (Persero), with the subject being PKP-PK personnel. This research is a qualitative descriptive study using the observation and literature study method by analyzing HR needs or the number of PKP-PK personnel, determining the number of maintenance technicians using the Allotment Hours method per year, calculating the minimum requirements and composition of PKP-PK personnel competencies according to the city category air force, and analysis of the competency qualifications of PKP-PK personnel in carrying out their main and main tasks. The results of this study indicate that the Organizational Structure and the number of PKP-PK unit personnel at Halim Perdanakusuma Airport have not met the standards required in accordance with the KP.14 regulation of 2015, the calculation results for determining the number of maintenance technicians using the Allotment Hours method per year PKP-PK Bandar unit Air Halim Perdanakusuma requires 1 personnel as a vehicle maintenance technician. And the efforts made in maintaining competence and licenses are by making a scheduled work program for training and exercise PKP-PK Halim Perdanakusuma Airport.